Le peuple elliptique : nouveau sujet politique et indigénéité d’État dans la Bolivie contemporaine - David Gomes (Centre de Recherches sur les Mondes Américains, 2013)
In the context of the radical political project led by President Evo Morales, the paper addresses the double issue of the creation of a new national imaginary and a novel political subject in contemporary Bolivia. A detailed analysis of the new Constitution captures the semantic changes towards intercultural plurality of its key concepts, such as « nation» or « people» , and its impact on the institutional architecture of the new model of multinational state, in particular through the multiple autonomies system. The results suggest that the adoption of a new state indigeneity, based on the historical recovery of the “indigenous” category, has propelled the latter to the level of almost consensual protagonist in the current national refounding process.